Pengaruh Kinerja Crewing Department terhadap Pergantian Jadwal Awak Kapal pada PT Pelita Global Logistik - Erika Chandra Wulandari; Intan Sianturi; ⁠Femmy Asdiana; Romanda Annas Amrullah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Changing crew schedules is an activity carried out routinely by the crewing department to carry out the process of crew on standby becoming crew on board or vice versa crew on board becoming crew on standby in accordance with the position and contract period that has been signed by each crew member in the PKL. This research is a quantitative descriptive study which aims to determine the effect of crewing department performance on crew schedule changes. The subjects in this research are the ship's crew and crewing department. Data collection in this research uses the method resulting from company crewing data with analysis techniques using simple liner regression analysis techniques which have positive and significant value in the validity test results and drawing conclusions from the research. The results of this research show that the performance of the crewing department has a big influence on crew schedule changes. From the results of the data analysis, the cause of the delay in changing the crew was due to several factors, including the crew changing the crew's schedule incorrectly with the ship's docking schedule, there were family problems where the crew asked to leave before their contract was completed, there were crew who off-hire and resigned, and the ship's crew change schedule does not match the PKL agreement because the crew has to extend the contract. So efforts that can be made to overcome the obstacles from this research are planning crew changes at least 3 months before each crew's contract period ends, not using extended contracts too often, making a backup schedule, and giving rewards or appreciation to the crew as a form of motivation.